Hebrew 'Idols' versus Greek 'Notions': Use and Translation of ' gillûlîm ' in Ezekiel - Holguin-Galvis, E. Carolina (Biblica, 2024)
Out of the thirty-five times that גלולים (gillûlîm, 'idols/dung gods') occurs in MT Ezekiel and are found in OG Ezekiel, the Greek translator(s) chose fifteen times ἐνθυμήματα ('imaginations'), three times διανοήματα/διάνοια ('thoughts/mind'), seven times ἐπιτηδεύματα ('practices'), and ten times εἴδωλα ('idols') to translate gillûlîm. This study contends that: 1) the translator(s) chose mental processes-related words (eighteen times) because of his (their) desire for relevance; and 2) OG Ezekiel contributes to developing the concepts of the nature of idols and the origin of impurity. Idols pollute the idolater not so much from the outside but mainly from the inside because it is the heart/mind that conceives and cultivates them.